2019
DOI: 10.1142/s2424862219500088
|View full text |Cite
|
Sign up to set email alerts
|

40 Years of Technological Innovation in China: A Review of the Four-Stage Climbing Track

Abstract: This paper combs the landscapes of China’s technological innovation practice during the 40 years of reform and opening up, and describes it as “Four-Stage Climbing” that is, “Learning–Introducing–Supplying Stage” (LIS Stage), “Introducing–Imitating–Improving Stage” (III Stage), “Integrating–Boosting–Creating Stage” (IBC Stage), and the “Innovating–Iterating–Promoting Stage” (IIP Stage). It also explains the background of each stage and its specific innovation model. Furthermore, the paper emphasizes the main f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…At this regional level, this study provides a specific standard to define the stage of innovation capacity development and how such a capacity evolves across different regions and over time. The results showed that China's RIC has experienced three states (i.e., low, medium, and high) that portrayed a similar pattern to that found by Lei et al [39], who argued that the development trajectory of China's technological innovation follows a process of "introducing-imitating-improving," "integrating-boosting-creating," and "innovating-iterating-promoting." However, this study further revealed the internal mechanism of a regional innovation system.…”
Section: Ric State Transitionsupporting
confidence: 69%
See 1 more Smart Citation
“…At this regional level, this study provides a specific standard to define the stage of innovation capacity development and how such a capacity evolves across different regions and over time. The results showed that China's RIC has experienced three states (i.e., low, medium, and high) that portrayed a similar pattern to that found by Lei et al [39], who argued that the development trajectory of China's technological innovation follows a process of "introducing-imitating-improving," "integrating-boosting-creating," and "innovating-iterating-promoting." However, this study further revealed the internal mechanism of a regional innovation system.…”
Section: Ric State Transitionsupporting
confidence: 69%
“…Since the reform and opening up in 1978, rapid development in terms of science, technology, and economy has been observed in China [39]. Specifically, China has made great effort in improving its innovation capacity.…”
Section: Technological Innovation In Chinamentioning
confidence: 99%
“…Innovation performance (PER) has been defined from diverse perspectives by scholars (Kumar & Chanda 2018;Lei, Liu, Qi, and Zhang 2019;Sharma and Chanda 2017). For instance, Utterback and Abernathy (1975) defined that innovation performance consists of product innovation and process innovation.…”
Section: Innovation Ecosystem and Innovation Performancementioning
confidence: 99%
“…Technological innovation is a main power to promote economic growth (Chen & Lei 2020;Chen & Xie 2018;Hämäläinen & Inkinen 2019;Kumar and Chanda 2018;Lei et al 2019Lei et al , 2020Lu 2016;Sui and Liu 2020;Tan et al 2010;Wang et al 2007;Wipulanusat et al 2020;Xu et al 2008Xu et al , 2011Xu et al , 2013Xu et al , 2016Xu et al , 2018Xu et al , 2020Viriyasitavat 2014, 2019;Yang et al 2018;Zhang et al 2018). Particularly, radical technological innovation generates substantial competitive advantages for enterprises (Li 2018(Li , 2020.…”
Section: Introductionmentioning
confidence: 99%